Mutations of Histidine 13 to Arginine and Arginine 5 to Glycine Are Responsible for Different Coordination Sites of Zinc(II) to Human and Murine Peptides. Issue 53 (27th August 2018) - Aliès, Bruno; Borghesani, Valentina; Noël, Sabrina; Sayen, Stephanie; Guillon, Emmanuel; Testemale, Denis; Faller, Peter; Hureau, Christelle
Abstract: Because mice and rats do not naturally develop Alzheimer's disease, genetically modified animals are required to study this pathology. This striking difference in terms of disease onset could be due to three alterations in the murine sequence (R5G, Y10F and H13R) of the amyloid‐β peptide with respect to the human counterpart. Whether the metal‐ion binding properties of the murine peptide are at the origin of such different amyloidogenicity of the two peptides is still an open question. Herein, the main zinc binding site to the murine amyloid‐β at physiological pH has been determined through the combination of several spectroscopic and analytical methods applied to a series of six peptides with one or two of the key mutations. These results have been compared with the zinc binding site encountered in the human peptide. A coordination mechanism that demonstrates the importance of the H13R and R5G mutations in the different zinc environments present in the murine and human peptides is proposed. The nature of the minor zinc species present at physiological pH is also suggested for both peptides. Finally, the biological relevance and fallouts of the differences determined in zinc binding to human versus murine amyloid‐β are also discussed. Abstract : Of mice and men : Zinc(II) coordination to murine amyloid‐β peptide is studied by using several complementary methods, in comparison with that of the human counterpart (see figure), and discussed with respect to different pathogenicities of the two peptides in Alzheimer's disease.